CONSUMEN MOTIVATION TO WARD INFORMATION SERVICE AND DRUG CONSULTATION OF PHARMACEUTICAL STORE IN YOGYAKARTA CITY - Ika Puspita Sari (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
Consumer perception and motivation study to drug information services has been performed in Jogjakarta. The result have shown that consumer motivation based on drive not the respon variable. For people it is important to get information services from drug store but its drug information is not enough for safety drug use, and it is difficult for them to acces drug information services in drug store.Key words : consumer perception, consumer motivation, drive, drug information services